The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0001-37652000000300011
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous overexpression of a transgene encoding the extracellular portion of the Drosophila Roughest-Irregular Chiasm C protein induces early embryonic lethality

Abstract: The cell adhesion molecule Rst-irreC is a transmembrane glycoprotein of the immunoglobulin superfamily involved in several important developmental processes in Drosophila, including axonal pathfinding in the optic lobe and programmed cell death and pigment cell differentiation in the pupal retina. As an initial step towards the "in vivo" functional analysis of this protein we have generated transgenic fly stocks carrying a truncated cDNA construct encoding only the extracellular domain of Rst-IrreC under the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(5 reference statements)
0
4
0
1
Order By: Relevance
“…We had previously shown that ubiquitous expression of a heat shock-inducible transgenic cDNA construct encoding the Rst protein ectodomain (pCa18D3.1) (Moda et al, 2000) at different embryonic stages can severely disrupt myogenesis by preventing myoblast fusion (Strünkelnberg et al, 2001) as well as block blastoderm cellularization and interfere with embryonic central nervous system midline formation (Moda and Ramos, unpublished). Induction of this construct during larval stages had no obvious developmental effects, but when white prepupae carrying pCa18D3.1 were heat shocked for a 22-hour period at 338C a small but consistent reduction in viability was observed in comparison with similarly treated nontransgenic siblings (see Fig.…”
Section: Misexpression Of the Rst Ectodomain Interferes With Salivarymentioning
confidence: 99%
See 2 more Smart Citations
“…We had previously shown that ubiquitous expression of a heat shock-inducible transgenic cDNA construct encoding the Rst protein ectodomain (pCa18D3.1) (Moda et al, 2000) at different embryonic stages can severely disrupt myogenesis by preventing myoblast fusion (Strünkelnberg et al, 2001) as well as block blastoderm cellularization and interfere with embryonic central nervous system midline formation (Moda and Ramos, unpublished). Induction of this construct during larval stages had no obvious developmental effects, but when white prepupae carrying pCa18D3.1 were heat shocked for a 22-hour period at 338C a small but consistent reduction in viability was observed in comparison with similarly treated nontransgenic siblings (see Fig.…”
Section: Misexpression Of the Rst Ectodomain Interferes With Salivarymentioning
confidence: 99%
“…Unless otherwise noted, all stocks used in this work were previously described (Araújo et al, 2003;Boschert et al, 1990;Lindsley and Zimm, 1992;Moda et al, 2000;Ramos et al, 1993).…”
Section: Fly Stocks and Genetic Manipulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in developmental processes mediated by cell adhesion molecules. Studies of Roughest (Rst) function have shown that its precise temporal expression is important for proper development (Araujo et al 2003) and ectopic expression of Rst leads to interference with its normal function (Schneider et al 1995;Reiter et al 1996;Moda et al 2000). Rst is a cell adhesion molecule of the immunoglobulin superfamily (Ramos et al 1993) functioning in several developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…A proteína Rst está envolvida em vários eventos no desenvolvimento de D. melanogaster, tais como a fusão de mioblastos durante a diferenciação da musculatura somática embrionária (STRÜNKELNBERG et al, 2001); o direcionamento axonal do lobo óptico (BOSCHERT et al, 1990; SCHNEIDER, 1995); a morfogênese de células precursoras interomatidiais (REITER et al 1996;ARAÚJO et al, 2003;BAO;CAGAN, 2005), a padronização dos órgãos sensoriais da antena (REDDY et al, 1999); diferenciação das células pigmentares do olho composto (ARAÚJO et al, 2003) e a morte celular programada no mesmo (WOLF; READY, 1991;RAMOS et al, 1993;REITER et al, 1996;ARAÚJO et al 2003); além da autofagia da glândula salivar larval (SIMON et al, 2009); foi também demonstrado que quando a porção extracelular desta proteína é superexpressa, ocorre uma interferência na celularização do blastoderma (MODA et al, 2000). Simon et al (2009) observaram que pupas portadoras de uma mutação dominante na região regulatória do gene roughest (rst D ) apresentaram suas glândulas larvais em períodos superiores a 16 horas após a formação do pupário, chegando até mesmo 24 horas após a formação do mesmo.…”
Section: 2o Gene Rstunclassified